Serological profile of John Cunningham virus (JCV) in patients with multiple sclerosis - Branco, Luciana Prats; Adoni, Tarso; Apostolos-Pereira, Samira Luisa; Brooks, Joseph Bruno Bidin; Correa, Eber Castro; Damasceno, Carlos Augusto; Eboni, Audred Cristina Biondo; Fezer, Leticia; Gama, Paulo Diniz da; Goncalves, Marcus Vinicius Magno; Gomes, Sidney; Grzesiuk, Anderson Kuntz; Mendes, Maria Fernanda; Morales, Rogerio Rizo; Muniz, Andre; Parolin, Monica Fiuza Koncke; Pimentel, Maria Lucia Vellutini; Ribeiro, Marlise de Castro; Santos, Gutemberg Augusto Cruz dos; Sato, Henry Koiti; Scherpenhuijzen, Simone Batista; Scorcine, Claudio; Siquineli, Fabio; Sousa, Nise Alexandra de Carvalho; Varela, Daniel Lima; Winckler, Tereza Cristina Avila; Fragoso, Yara Dadalti (Arquivos de Neuro-Psiquiatria, 2018)
Treatment options for multiple sclerosis (MS) have changed over the last few years, bringing about a new category of drugs with more efficient profiles. However, these drugs have come with a whole new profile of potential adverse events that neurologists have to learn well and quickly. One of the most feared complications of these MS treatments is progressive multifocal leukoencephalopathy caused by the reactivation of the John Cunningham virus (JCV). Objective: To identify the serologic profile of JCV in patients with MS. Methods: Data on serum antibodies for JCV were obtained using the enzyme-linked immunosorbent assay provided by the STRATIFY-JCV program. Results: A total of 1,501 blood tests were obtained from 1,102 patients with MS. There were 633 patients (57.1%) who were positive for antibodies for JCV and 469 patients who were negative (42.9%). Twenty-three patients became positive after initially having negative JCV antibody status. The rate of seroconversion was 18.5% over 22 months. Conclusion: The JCV serologic profile and seroconversion in Brazilian patients were similar to those described in other countries.
Keywords: multiple sclerosis; leukoencephalopathy, progressive multifocal; JC virus; natalizumab